It's instruction over place — not the other way around!. (December 2016) - Kauffman, James M.; Badar, Jeanmarie
Full inclusion of students with disabilities focuses on where students are taught, not on instruction. The idea that all students, including those with disabilities, can and should be taught together in the same class and school is a highly prized myth. Focusing on inclusion rather than on appropriate instruction and on a continuum of alternative placements is illogical as well as illegal. It's also stressful for teachers, most of whom are unable to teach such a learning-diverse group of students in a single classroom and do it well. Responsible inclusion requires recognizing individual differences and being more concerned about appropriate, effective instruction than about where a student is taught .